The genus Biroia Szépligeti, 1900 (Hymenoptera, Braconidae, Agathidinae) in China, with description of two new species - Tang, Pu; Liu, Zhen; Chen, Xue-Xin (Zootaxa, 2012)
Three Chinese species of Biroia Szépligeti, 1900 are recognized. Two new species, B. hirsutus sp. nov., B. baishanzuensis sp. nov., are described and illustrated. A new synonym is proposed, B. bicolor (Wang, 1984) with B. taeniocauda (Enderlein, 1920). A key to the Chinese species of the genus Biroia is provided.